Potential of Proteolytic Bacteria from Vegetable and Fruit Waste-Based Eco-Enzyme : Potensi Bakteri Proteolitik dari Eco-Enzyme Berbasis Limbah Sayuran dan Buah - Satitiningrum, Yuni; Ulmillah, Aulia; Haryanti, Yesi (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
Organic waste, often considered useless material, can be processed into value-added products such as eco-enzymes. Eco-enzyme is a liquid fermented from organic waste that contains various enzymes, including proteases. This study aims to explore the potential of proteolytic bacteria from eco-enzyme solutions made from vegetable and fruit waste and analyze the proteolytic index of the isolates obtained. This research applied a quantitative approach with descriptive methods. The isolation technique used in this research is the pour plate method with milk agar media, which calculates the number of bacterial colonies using the TPC (Total Plate Count) formula. The results showed that nine bacterial isolates were obtained from the isolation of vegetable and fruit waste-based eco-enzyme solution. Qualitative tests showed that isolate 8A had the highest proteolytic index of 5, while isolate 7B had the lowest proteolytic index of 1.5.